2018
DOI: 10.1007/s10711-018-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Topological and Hodge L-classes of singular covering spaces and varieties with trivial canonical class

Abstract: The signature of closed oriented manifolds is well-known to be multiplicative under finite covers. This fails for Poincaré complexes as examples of C. T. C. Wall show. We establish the multiplicativity of the signature, and more generally, the topological L-class, for closed oriented stratified pseudomanifolds that can be equipped with a middle-perverse Verdier self-dual complex of sheaves, determined by Lagrangian sheaves along strata of odd codimension (so-called L-pseudomanifolds). This class of spaces cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…The conjecture holds for simplicial projective toric varieties as shown by Maxim and Schürmann [29, Corollary 1.2(iii)]. Furthermore, the conjecture was established by the first author in [5] for normal connected complex projective threefolds X$X$ that have at worst canonical singularities, trivial canonical divisor, and prefixdimH1(X;scriptOX)>0$\operatorname{dim} H^{1}(X; \mathcal {O}_{X}) > 0$. Generalizing the above cases, Fernández de Bobadilla and Pallarés [17] proved the conjecture for all compact complex algebraic varieties that are rational homology manifolds.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The conjecture holds for simplicial projective toric varieties as shown by Maxim and Schürmann [29, Corollary 1.2(iii)]. Furthermore, the conjecture was established by the first author in [5] for normal connected complex projective threefolds X$X$ that have at worst canonical singularities, trivial canonical divisor, and prefixdimH1(X;scriptOX)>0$\operatorname{dim} H^{1}(X; \mathcal {O}_{X}) > 0$. Generalizing the above cases, Fernández de Bobadilla and Pallarés [17] proved the conjecture for all compact complex algebraic varieties that are rational homology manifolds.…”
Section: Introductionmentioning
confidence: 89%
“…Conversely, let us show that 𝑋 𝑎 (𝐸 * ) ∩ 𝑋 𝑏 (𝐹 * ) ⊂ 𝑆(𝑋 𝑎 ′ (𝐸 ′ * ) × 𝑋 𝑎 ′′ (𝐸 ′′ * )) in (5). Given 𝑃 ∈ 𝑋 𝑎 (𝐸 * ) ∩ 𝑋 𝑏 (𝐹 * ), we set 𝑃 ′ = 𝑃 ∩ 𝐸 𝑛 ′ and 𝑃 ′′ = 𝑃 ∩ 𝐹 𝑛 ′′ , and note that dim ℂ (𝑃 ′ ) = dim ℂ (𝑃 ∩ 𝐸 𝑛 ′ ) ⩾ dim ℂ (𝑃 ∩ 𝐸 𝑎 𝑘+1−𝑘 ′ +𝑘 ′ ) ⩾ 𝑘 ′ because 𝑃 ∈ 𝑋 𝑎 (𝐸 * ) (where we note that 𝐸 𝑎 𝑘+1−𝑘 ′ +𝑘 ′ ⊂ 𝐸 𝑛 ′ holds because 𝑎 𝑘 ′′ +1 ⩽ 𝑚 ′ implies that 𝑎 𝑘+1−𝑘 ′ + 𝑘 ′ ⩽ 𝑛 ′ ), and dim ℂ (𝑃 ′′ ) = dim ℂ (𝑃 ∩ 𝐹 𝑛 ′′ ) = dim ℂ (𝑃 ∩ 𝐹 𝑏 𝑘+1−𝑘 ′′ +𝑘 ′′ ) ⩾ 𝑘 ′′ because 𝑃 ∈ 𝑋 𝑏 (𝐹 * ) (where we note that 𝐹 𝑏 𝑘+1−𝑘 ′′ +𝑘 ′′ = 𝐹 𝑛 ′′ holds because 𝑏 𝑘 ′ +1 = 𝑚 ′′ implies that 𝑏 𝑘+1−𝑘 ′′ + 𝑘 ′′ = 𝑛 ′′ ).…”
Section: Segre Products In Ambient Grassmanniansmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavior of the L-class for singular spaces under Gysin transfers associated to finite degree covers is already completely understood. In [5], we showed that for a closed oriented Whitney stratified pseudomanifold X admitting Lagrangian structures along strata of odd codimension (e.g. X Witt) and p : X ′ → X an orientation preserving topological covering map of finite degree, the L-class of X transfers to the L-class of the cover, i.e.…”
Section: Introductionmentioning
confidence: 99%